NÍVEIS DE IgG1, IgG2, IgG3 E IgG4 ESPECÍFICOS A ANTÍGENOS DE POLÉN DE Lolium multiflorum EM PACIENTES COM POLINOSE NO SUL DO BRASIL - Silva, Karina Santos (2024)
Pollinosis is a seasonal allergic rhinitis that occurs when exposure to aeroallergens, such as grass pollen, triggers an inflammatory process, causing a respiratory allergic response in sensitized individuals. Sensitization to an allergen demonstrates the allergen's ability to provoke a Th2 cell response, while IL-4 and IL-13 stimulate IgE production, inducing class switching of immunoglobulins in B cells. The study involved 50 participants, both men and women, aged between 15 and 61 years, diagnosed with seasonal allergic rhinitis in Caxias do Sul, RS. Among them, 39 individuals (17 men, 43.59% / 22 women, 56.41%) had positive results in both the skin prick test (SPT) and the ELISA-IgE specific for Lolium multiflorum (Lm) pollen extract. Additionally, 11 individuals with negative results in both the SPT and the ELISA-IgE were selected as the control group. Statistical significance was considered with p < 0.05. A correlation analysis was performed to examine the relationship between specific antibodies to the Lm extract and the size of the wheal. The analysis revealed that specific anti-Lm IgG antibody levels did not show a significant correlation with the SPT results, both in atopic (r=0.1443; p=0.3278) and non-atopic (r=-0.01537; p=0.9174) individuals. However, a strong positive correlation was observed between specific IgE levels and SPT results (r=0.6024; p<0.0001). IgE levels showed a strong correlation with SPT reactivity, while IgG subclasses displayed weak or no significant correlation. This suggests that the IgE-mediated allergic response in pollinosis operates independently of specific IgG. Understanding these immune responses in atopic and non-atopic individuals is crucial for personalizing allergy treatments, especially in allergen-specific immunotherapy (AIT), where modulation of the immune response through IgG4 may have a significant impact.